Pengaruh Faktor-Faktor Akuisisi terhadap Abnormal Return (Studi pada Perusahaan Akuisitor di BEJ antara Tahun 1992 Sampai 1997) - Ali Muktiyanto (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2005)
The objective of this study are (1) to examine the change the abnormal returns pre and post acquisition, (2) to examine the influence of acquisition factors: Q ratio (Tobin’s Q ratio), relative size between bid¬der and target acquisition (size), reaction target management (hostile or fiendly/HF), choice of investment financ¬ing/COI), number of bidder acquisition (number of bidder/NB) and asymmetric information (AI), on the companies’ abnormal returns either simultaneously or partially, and (3) to examine the influence acquisition factors on the abnormal returns in case of internal and external acquisition.By analyzing financial statement of 20 bidders and 40 target conducted acquisition at Bursa Efek Ja¬karta between 1992 and 1997, the result of the study shows that (1) the companies abnormal returns have posi¬tive performance, (2) the acquisition factors in both simultaneously and partially have positive influence on the ab¬normal returns, and (3) there is a different influence of acquisition factors on the abnormal returns between inter¬nal acquisition and those of external acquisition.Key words: acquisition, abnormal return, bidder, target